2011
DOI: 10.1016/j.jacc.2011.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Double-Edged Role of the CXCL12/CXCR4 Axis in Experimental Myocardial Infarction

Abstract: CXCR4 plays a crucial role in endogenous remodeling processes after MI, contributing to inflammatory/progenitor cell recruitment and neovascularization, whereas its deficiency limits infarct size and causes adaptation to hypoxic stress. This should be carefully scrutinized when devising therapeutic strategies involving the CXCL12/CXCR4 axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 31 publications
3
113
0
3
Order By: Relevance
“…32 In line with these results, the infarct size was significantly reduced in miR-150 + mice. Downregulation of miR-150 resulted in the opposite effect.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…32 In line with these results, the infarct size was significantly reduced in miR-150 + mice. Downregulation of miR-150 resulted in the opposite effect.…”
Section: Discussionsupporting
confidence: 65%
“…13 In the present study, CXCR4 levels were reduced in miR-150 + monocytes in vivo and ex vivo. Similarly, a recent study 32 revealed that CXCR4 +/-mice displayed diminished levels of Gr1 high monocytes, smaller and stable AMI, and impaired myocardial neovascularization after AMI. This is keeping in line with mice, which overexpressed miR-150 after AMI, implying that CXCR4 has an important role in the physiological response of miR-150 to acute ischemic injury.…”
Section: Discussionmentioning
confidence: 70%
“…Similar beneficial effects of CXCR4 blockade have also been observed for myocardial infarction. 41 Here, a genetic approach was used to show that CXCR4 deficiency reduces infarct size by attenuating initial neutrophil influx and by causing adaptation to hypoxic stress. 41 As the CXCR4 inhibitor, AMD3100, has already been approved for shortterm administration under certain conditions in humans, these results further indicate a certain potential for the development as a pharmacological therapy for stabilizing AAA.…”
Section: Abdominal Aortic Aneurysmmentioning
confidence: 99%
“…This dual approach, using stem-cell transplantation and genetic engineering to potentiate stem cell activity for myocardial repair, seems to be a reliable method and is currently successfully used in many experimental settings. [17][18][19][20][21] As an example, overexpressing stromal derived factor-1 (CXCL12), an important chemokine in cardiac development, protects the myocardium and sustains the repairing after myocardial infarction, 22 by promoting regeneration and angiogenesis through recruitment of progenitor cells. 23,24 Notably, the vasoregenerative and angiogenic potential of angiogenic early outgrowth cells can be enhanced by the transfer of the CXCL12 receptor CXCR4 through platelet microparticles.…”
Section: Article See P 312mentioning
confidence: 99%